Prolonged co-treatment with HGF sustains epithelial integrity and improves pharmacological rescue of Phe508del-CFTR - Ana M. Matos (Scientific Reports, 2018)
Abstract Cystic fibrosis (CF), the most common inherited disease in Caucasians, is caused by mutations in the CFTR chloride channel, the most frequent of which is Phe508del. Phe508del causes not only intracellular retention and premature degradation of the mutant CFTR protein, but also defective channel gating and decreased half-life when experimentally rescued to the plasma membrane (PM). Despite recent successes in the functional rescue of several CFTR mutations with small-molecule drugs, the folding-corrector/gating-potentiator drug combinations approved for Phe508del-CFTR homozygous patients have shown only modest benefit. Several factors have been shown to contribute to this outcome, including an unexpected intensification of corrector-rescued Phe508del-CFTR PM instability after persistent co-treatment with potentiator drugs. We have previously shown that acute co-treatment with hepatocyte growth factor (HGF) can significantly enhance the chemical correction of Phe508del-CFTR. HGF coaxes the anchoring of rescued channels to the actin cytoskeleton via induction of RAC1 GTPase signalling. Here, we demonstrate that a prolonged, 15-day HGF treatment also significantly improves the functional rescue of Phe508del-CFTR by the VX-809 corrector/VX-770 potentiator combination, in polarized bronchial epithelial monolayers. Importantly, we found that HGF treatment also prevented VX-770-mediated destabilization of rescued Phe508del-CFTR and enabled further potentiation of the rescued channels. Most strikingly, prolonged HGF treatment prevented previously unrecognized epithelial dedifferentiation effects of sustained exposure to VX-809. This was observed in epithelium-like monolayers from both lung and intestinal origin, representing the two systems most affected by adverse symptoms in patients treated with VX-809 or the VX-809/VX-770 combination. Taken together, our findings strongly suggest that co-administration of HGF with corrector/potentiator drugs could be beneficial for CF patients.